Integrated petrophysical evaluation of a heterogeneous shaly-sand reservoir: A case study in nahr umr formation-subba giant oil field, Iraq - Jaber, A.K. (Maxwell Science Publications, 2014)
This study presents an integrated petrophysical evaluation for Nahr Umr reservoir by highlighting a practical trustworthy approach petrophysical model for Nahr Umr reservoir in Subba oil field depending on available data. The available data include core analysis conducted on seven core samples taken from seven wells in Subba oil field and well set logs which include gamma ray, static spontaneous, neutron, sonic, density and resistivity logs. Subba oil field is a giant oil field located in southern part of Iraq about 110 km Northwest Basra. Nahr Umr formation in Subba oil field is a heterogeneous clastic reservoir. It was considered one of the most important producing clastic reservoir in southern Iraqi oil fields. The conventional petrophysical models, by using neutron-density cross-plot for lithology and porosity and Archie's equation for water saturation, can be adequate for evaluating clean sands. Usually the shaly sand formations are adhere to bad hole in shale section. Facies identification was achieved depending on core analysis data, core description data and wire line log measurements. The calculations of permeability was based on rock types identification and using available core data measurements. The generated permeability models can be used to calculate permeability for uncored intervals in all wells corresponding to each facies. Porosity was calculated using Neutron-density porosity model and Sonic model for bad hole section. Saturation model was built by utilizing the Indonesia Equation model, this model has proved its efficiency to be applied successfully for clastic Iraqi reservoirs. The petrophysical parameters were determined on a well-by-well basis. The formation resistivity factors (a, m) and water saturation exponent (n) have been derived from Pickett plot and formation water salinity. Reservoir quality calculations or net pay values are based on cut-offs values for porosity, saturation and shale volume. Â© Maxwell Scientific Organization, 2014.